1996
DOI: 10.1093/rheumatology/35.6.589
|View full text |Cite
|
Sign up to set email alerts
|

Phosphattdyl Serine-Dependent Antiprothrombin Antibody Is Exclusive to Patients With Lupus Anticoagulant

Abstract: We conducted this study to determine whether antiprothrombin antibody (aPT) [to prothrombin (PT) alone or PT/phosphatidyl serine (PS) complex] actually existed in patients with lupus anticoagulant (LA) and/or anticardiolipin antibody (aCL). aPT to PT alone was positive in 2/7 LA-positive (29%) and 3/7 LA/aCL-positive (43%) patients. aPT to PT/PS complex was positive in 4/7 LA-positive (57%) and 4/7 LA/aCL-positive (57%) patients in the presence of Ca2+. However, none of the aCL-positive patients without LA or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 13 publications
3
20
1
Order By: Relevance
“…In this regard, we reported recently that ␤2GPI itself functions as an inhibitor of phospholipid-dependent anticoagulant activity of APC (49). The clustering mechanism proposed in this study may also explain the anti-APC activity of anti-␤2GPI antibodies observed in previous studies (64)(65)(66), and indeed, anti-␤2GPI mAbs used in the current study were found to have a potent inhibitory activity against the anticoagulant activity of APC (our unpublished data).…”
Section: Discussionsupporting
confidence: 79%
“…In this regard, we reported recently that ␤2GPI itself functions as an inhibitor of phospholipid-dependent anticoagulant activity of APC (49). The clustering mechanism proposed in this study may also explain the anti-APC activity of anti-␤2GPI antibodies observed in previous studies (64)(65)(66), and indeed, anti-␤2GPI mAbs used in the current study were found to have a potent inhibitory activity against the anticoagulant activity of APC (our unpublished data).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, aPT was exclusively positive in patients with LA (6/15, 40 . 0%), further suggesting that PT may be the target antigen of LA and that aPT may be the same entity as LA as previously reported (Matsuda et al, 1996).…”
supporting
confidence: 80%
“…This speculation may be further supported by the evidence that both aCL/AECA-positive sera absorbed with cardiolipin liposome/b 2 -GPI became aCL-negative, but still retained AECA reactivity. Furthermore, both aPT/AECA-positive sera absorbed with phosphatidylserine-liposome/prothrombin, which is regarded as the target antigen of LA (Beevers et al, 1991;Oosting et al, 1993;Matsuda et al, 1996), still retained AECA reactivity.…”
Section: Discussionmentioning
confidence: 96%
“…We also confirmed the existence of aPT in 40% of systemic lupus erythematosus (SLE) patients with LA by ELISA, employing a non-y-ray-irradiated plain plate, but we failed to detect aPT when we employed a y-ray-irradiated plate [2,3].…”
Section: Introductionsupporting
confidence: 58%